2020
DOI: 10.1007/s00520-020-05519-5
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: the effect of right hemicolectomy for cancer on postoperative bowel function

Abstract: Background Right-sided cancer accounts for approximately 30% of bowel cancer in women and 22% in men. Colonic resection can cause changes in bowel function which affect daily activity. The aims are to assess the impact of right hemicolectomy for cancer on bowel function and to identify useful treatment modalities for managing bowel dysfunction after right hemicolectomy. Method The review was conducted in line with PRISMA. Eligible studies evaluated the impact of right hemicolectomy on bowel function in those t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 52 publications
1
24
0
Order By: Relevance
“…While colonic dysmotility seems to contribute to LARS after colon cancer surgery as well, the reduced absorptive capacity of electrolytes and water probably results in more liquid stool, increased bowel frequency and the risk for faecal incontinence ( 9 , 25 27 ). In accordance to the existing literature, the present study observed that LARS complaints were most prevalent in colon cancer patients after a sigmoid resection or right hemicolectomy ( 9 , 11 , 25 , 27 , 28 ). Most likely, the reduced reservoir capacity of the rectum when incorporated in an anastomosis is an additional factor contributing to these complaints after a sigmoid resection ( 10 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…While colonic dysmotility seems to contribute to LARS after colon cancer surgery as well, the reduced absorptive capacity of electrolytes and water probably results in more liquid stool, increased bowel frequency and the risk for faecal incontinence ( 9 , 25 27 ). In accordance to the existing literature, the present study observed that LARS complaints were most prevalent in colon cancer patients after a sigmoid resection or right hemicolectomy ( 9 , 11 , 25 , 27 , 28 ). Most likely, the reduced reservoir capacity of the rectum when incorporated in an anastomosis is an additional factor contributing to these complaints after a sigmoid resection ( 10 ).…”
Section: Discussionsupporting
confidence: 91%
“…Most likely, the reduced reservoir capacity of the rectum when incorporated in an anastomosis is an additional factor contributing to these complaints after a sigmoid resection ( 10 ). While after a right hemicolectomy, the loss of the right colon, which is considered as the main site for water absorption, might contribute to the increased risk for complaints ( 25 , 28 ). Besides, the loss of the ileocaecal valve and its sphincter function, the consequent ileocolic dysmotility and the increased malabsorption of bile acids in the terminal ileum may also declare the increased bowel complaints observed after a right hemicolectomy ( 25 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While urgency is common among colon cancer survivors in general, patients who have undergone right‐sided resection suffer from increased defaecation frequency, loose stools and nocturnal defaecation. Patients who have undergone left‐sided resection often have fragmentation, a feeling of obstruction and require a long time for evacuation [4–7]. Importantly, most symptoms can be relieved if patients are treated properly [8].…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that colorectal cancer (CRC) develops from a series of precursor epithelial polyps [1], which include conventional adenomas, incorporating tubular adenomas and villous/tubulovillous adenomas (VA/TVA) and serrated polyps, incorporating hyperplastic polyps (HP), sessile serrated adenomas (SSA) and traditional serrated adenomas (TSA). VA/TVAs are thought to be the advanced precursors in the "adenoma-carcinoma" pathway [2]. Risk factors include advancing age, male gender, highfat, low-fiber diet, tobacco use, and excess alcohol intake (more than eight drinks a week).…”
Section: Introductionmentioning
confidence: 99%